2014
DOI: 10.1227/neu.0000000000000256
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Blood Pressure Management During Carotid Endarterectomy and Early Cognitive Dysfunction

Abstract: Background A common practice during cross-clamp of carotid endarterectomy (CEA) is to manage mean arterial pressure (MAP) above baseline to optimize collateral cerebral blood flow and reduce risk of ischemic stroke. Objective To determine whether MAP management ≥20% above baseline during cross-clamp is associated with lower risk of early cognitive dysfunction, a subtler form of neurologic injury than stroke. Methods One hundred eighty-three patients undergoing CEA were enrolled in this ad hoc study. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…Overall, 64 full text articles were assessed. Of these, 40 did not meet our inclusion criteria and 9 articles (30)(31)(32)(33)(34)(35)(36)(37)(38) were excluded due to suspected duplicate reporting (19,26,27,39). In total, 15 articles were included.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 64 full text articles were assessed. Of these, 40 did not meet our inclusion criteria and 9 articles (30)(31)(32)(33)(34)(35)(36)(37)(38) were excluded due to suspected duplicate reporting (19,26,27,39). In total, 15 articles were included.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies different methods of neuropsychological testing were implemented, including MMSE [ 29 , 34 , 35 , 36 ], various batteries of popular neuropsychometric tests (for example, Williams-Russo [ 28 ] used a battery of 10 tests, Panda [ 31 ] 7 tests and Moller [ 12 ] 4 different tests) and some self-developed ones (Heyer et al [ 32 ]). Such diversity and lack of standardization impedes the drawing of reliable conclusions and does not allow to formulate recommendations for clinicians for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Heyer et al assessed the influence of intraoperative BP on early cognitive deficit in 183 patients undergoing cross-clamp open carotid endarterectomy under general anesthesia between 1995 and 2012 [ 32 ]. They found that patients whose intraoperative MAP was maintained ≥ 20% of baseline values, exhibited an 82% lower risk of POCD ( p < 0.001).…”
Section: Reviewmentioning
confidence: 99%
“…According to previous literature, the post-operative blood pressure was maintained 10e20% lower than pre-operative levels, not >160 mmHg. 19,20 Furthermore, the blood pressure was tightly monitored and timely regulated according to patients' symptoms before discharging from the ICU. Eleven antihypertensive drugs were administered to different patients.…”
Section: Discussionmentioning
confidence: 99%